Expression of an Endopeptidase (EP-C1) in Phaseolus vulgaris Plants. - Tanaka, T. (1993)
Endopeptidase activity increases continually in pods of maturing fruits of French bean (Phaseolus vulgaris L. cv Goldstar) plants and is thought to participate in the protein mobilization in pods during the development of seeds (M. Endo, T. Minamikawa, D. Yamauchi, W. Mitsuhashi [1987] J Exp Bot 38: 1988-1995). In the present studies, one of the major endopeptidase forms, designated EP-C1, was purified as a 34-kD polypeptide from pods of maturing French bean fruits. EP-C1 was found to be immunologically distinguished from other forms in extracts from pods, but homologous to SH-EP, the major cysteine endopeptidase expressed in cotyledons of germinating Vigna mungo seeds (W. Mitsuhashi, T. Minamikawa [1989] Plant Physiol 89: 274-279). The level of endopeptidase that reacted with the antiserum to EP-C1 increased in pods as the fruit maturation proceeded. EP-C1 was also immunologically detected in stems of French bean plants bearing fruits of later maturation stages. Protein immunoblotting showed that a 34-kD polypeptide corresponding to EP-C1 in molecular mass occurred in extracts from 7- to 9-d cotyledons of germinating French bean seeds. In addition, two other polypeptides with slightly higher molecular masses were observed in extracts from 3- to 5-d cotyledons. We suggest that these two polypeptides are intermediates involved in posttranslational processing of EP-C1. RNA blot hybridization with EP-C1 cDNA as a probe showed that EP-C1 mRNA occurred in pods of fruits at later maturing stages and also in cotyledons of 3- to 7-d germinating seeds.